Brain iron and metabolic abnormalities in C19orf12 mutation carriers: A 7.0 tesla MRI study in mitochondrial membrane protein–associated neurodegeneration. Issue 1 (13th September 2019) - Dusek, Petr; Mekle, Ralf; Skowronska, Marta; Acosta‐Cabronero, Julio; Huelnhagen, Till; Robinson, Simon Daniel; Schubert, Florian; Deschauer, Marcus; Els, Antje; Ittermann, Bernd; Schottmann, Gudrun; Madai, Vince I.; et al.
Abstract: Background: Mitochondrial membrane protein‐associated neurodegeneration is an autosomal‐recessive disorder caused by C19orf12 mutations and characterized by iron deposits in the basal ganglia. Objectives: The aim of this study was to quantify iron concentrations in deep gray matter structures using quantitative susceptibility mapping MRI and to characterize metabolic abnormalities in the pyramidal pathway using 1 H MR spectroscopy in clinically manifesting membrane protein‐associated neurodegeneration patients and asymptomatic C19orf12 gene mutation heterozygous carriers. Methods: We present data of 4 clinically affected membrane protein‐associated neurodegeneration patients (mean age: 21.0 ± 2.9 years) and 9 heterozygous gene mutation carriers (mean age: 50.4 ± 9.8 years), compared to age‐matched healthy controls. MRI assessments were performed on a 7.0 Tesla whole‐body system, consisting of whole‐brain gradient‐echo scans and short echo time, single‐volume MR spectroscopy in the white matter of the precentral/postcentral gyrus. Quantitative susceptibility mapping, a surrogate marker for iron concentration, was performed using a state‐of‐the‐art multiscale dipole inversion approach with focus on the globus pallidus, thalamus, putamen, caudate nucleus, and SN. Results and Conclusion: In membrane protein‐associated neurodegeneration patients, magnetic susceptibilities were 2 to 3 times higher in the globus pallidus ( P = 0.02) and SN ( P = 0.02) compared to controls. In addition, significantly higher magnetic susceptibility was observed in the caudate nucleus ( P = 0.02). Non‐manifesting heterozygous mutation carriers exhibited significantly increased magnetic susceptibility (relative to controls) in the putamen ( P = 0.003) and caudate nucleus ( P = 0.001), which may be an endophenotypic marker of genetic heterozygosity. MR spectroscopy revealed significantly increased levels of glutamate, taurine, and the combined concentration of glutamate and glutamine in membrane protein‐associated neurodegeneration, which may be a correlate of corticospinal pathway dysfunction frequently observed in membrane protein‐associated neurodegeneration patients. © 2019 International Parkinson and Movement Disorder Society